تشخيص واقع التمويل المحلي في الجزائر - بوعيساوي, محجوب (جامعة الوادي - University of Eloued, 2021)
حاولنا من خلال هذه الورقة البحثية للتطرق لأهم المشاكل التي تميز الجماعات المحلية المشكلة في الجزائر من الولاية والبلدية المتمثلة في ضعف التمويل المحلي، الذي بالرغم من تعدد مصادره المتمثلة في الموارد الداخلية والمشكلة من الضرائب والرسوم و مداخيل الممتلكات للجماعات المحلية والمصادر الخارجية المشكلة من مختلف الإعانات والتخصيصات التي تخصصها السلطات المركزية ضمن ميزانية الدولة أو عن طريق صندوق التضامن والضمان للجماعات المحلية ،إلا أنها تبقى ضعيفة نتيجة لضعف الجباية المحلية مقارنة بالجباية العادية للدولة أو لعدم استقرار الإعانات والمخصصات التي تأتي من ميزانية الدولة خاصة وان هاته الأخيرة مرتبطة بمداخيل الجباية المحلية ، هذا ماجعل المشرع الجزائري في كل مرة يقوم بفتح ورشات إصلاحية هدفها إنعاش التمويل المحلي بما يضمن تنمية محلية مستديمة Through this research paper, we tried to address the most important problems that distinguish the Local Administration formed in Algeria from the state and the municipality; Represented by the weakness of local finance ,which despite its multiple sources of internal resources consisting of taxes fees, and property incomes for local administration and external sources. They are made up of various subsidies, and allocations allocated by the central authorities within the State budget, or through the solidarity and guarantee fund for local groups. However, it remains weak as a result of the weakness of local collection compared to the regular collection of the state, or the instability of subsidies and allocations that come from the state budget. Especially since the latter is linked to the local local taxes income. This is what made the Algerian legislator every time to opened reform workshops, aimed at reviving local finance to ensure sustainable local development.
Diagnosing the reality of local finance in Algeria
مقال
Keywords: التمويل المحلي، الجباية المحلية، اللامركزية، إصلاح التمويل المحلي،